Drug Abuse Prevention Among Students In Improving The Lives Meaning Through Counseling Logo - Kadek Suranata (Indonesian Institute for Counseling, Education and Therapy (IICET), 2013)
Abuse of drugs, psychotropic substances, illegal drugs and other addictive substances (drugs) among teenagers especially students to be a problem from time to time keeps going on and it seems difficult to be finalized. So also in Indonesia drug abuse prevention efforts at the level of the student and the student assessment has been a great school for education practitioners and also involving relevant agencies such as BNN, BKKBN, the health department and the police. On the other hand, the number of victims of drug abuse among adolescents from year-to-year increase. spiritual intelligence (SQ) is low is one of the students to be drug users. Various approaches, models and techniques of counseling has been developed and implemented in schools in order to develop students' potential. Counseling logo is one of the counseling intervention model that was first introduced by Viktor Frankl who seek to build the spiritual dimension of human besides raceway and psychological dimensions, and assume that the meaning of life and a desire for meaningful is the primary motivation of men to achieve meaningful livelihoods (the meaningful life) is wanted. This research aimed to develop the logo counseling to improving the lives meaning drug abuse prevention and to know the effectiveness of that model. This research uses research and development approach or R&D with seven essential steps, namely (1) research and information collecting, (2) planning, (3) developing preliminary from of product, (4) preliminary field testing and product revision, (5) main field test and product revision, (6) operational field test and product revision, and (7) dissemination implementation and institutionalization. The population of this research includes practitioners or school counselors, experts and both state, Junior High School, Senior High Scholl and vocational students in Bali Province. The results of research on the effect of counseling logo on the trend of drug abuse in students in Singaraja shows that students who attend counseling logo managed to increase the meaning of life and reduces the tendency of involvement in drug abuse.